Characteristics of Convex Skin Barriers and Clinical Application: Results of an International Consensus Panel. Issue 6 (November 2021) - McNichol, Laurie; Cobb, Terri; Depaifve, Yves; Quigley, Mary; Smitka, Kimberly; Gray, Mikel
Abstract : Regulatory bodies do not set parameters for measuring certain ostomy product characteristics. As a result, each manufacturer has a different way of measuring specific convex skin barrier characteristics that may create confusion among clinicians when selecting a product. In order to alleviate this confusion and encourage consistency in reporting product characteristics, an international meeting of clinicians with expertise in the care of persons living with an ostomy was convened. The goal of the meeting was to define and establish consistency in convex skin barrier characteristics and their clinical application of the product based on these characteristics. Twelve nurse panelists from 11 countries reviewed, discussed, and reached consensus on a group of proposed statements designed to provide standard definitions of convex skin barrier characteristics and clinically relevant application. The group reached consensus on 5 characteristics of convex skin barriers: depth, compressibility, flexibility, slope, and tension location. These statements provide a basis for quantifying the most clinically relevant characteristics of convex skin barriers and a framework for their application in clinical practice.